1991
DOI: 10.1161/01.hyp.18.6.758
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of agonist-evoked platelet Ca2+ in hypertensive rats.

Abstract: We previously reported an enhanced peak response of intracellular free Ca 2+ to thrombin in platelets of spontaneously hypertensive rats in comparison with normotensive Wistar-Kyoto rats. In the present study, we compared the platelet intracellular Ca 2+ response to the receptor-linked agonist thrombin with the response to the Ca 2+ ionophore ionomycin. Basal intracellular Ca 2+ was higher in hypertensive platelets as was leakage of fura-2. We confirmed the previous finding that the thrombin-induced intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As described earlier, 1 mM CaCl 2 was added and allowed to equilibrate for 5 min, and then 5 mM EGTA was added to chelate extracellular Ca 2ϩ (the external Ca 2ϩ concentration was Ͻ10 Ϫ8 M). Ionomycin (5 M) was added 1 min later, and the peak [Ca 2ϩ ] i was used as an estimate of the Ca 2ϩ in the dense tubular system (DTS), which is the intracellular Ca 2ϩ storage site in platelets (31).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…As described earlier, 1 mM CaCl 2 was added and allowed to equilibrate for 5 min, and then 5 mM EGTA was added to chelate extracellular Ca 2ϩ (the external Ca 2ϩ concentration was Ͻ10 Ϫ8 M). Ionomycin (5 M) was added 1 min later, and the peak [Ca 2ϩ ] i was used as an estimate of the Ca 2ϩ in the dense tubular system (DTS), which is the intracellular Ca 2ϩ storage site in platelets (31).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Hypertensive patients and normotensive controls were maintained on a regular diet with an intake of 170 mmol/day NaCl to allow stabilization of the systemic Na ϩ balance, and they ingested constant amounts of K ϩ (2,000 mg/day), Ca 2ϩ (500 mg/day), and calories (40 kcal/kg) for 7 days before the study. Venous blood was collected from fasting and resting subjects, slowly and steadily via a 19-gauge needle into a syringe containing 3.8% trisodium citrate (1:9 by vol, total 30 ml), using a two-syringe method (21) ] i was measured as described previously (13,21,22). In short, plateletrich plasma prepared as described above was layered onto a Sepharose 2B-CL column (Pharmacia LKB Biotechnology, Uppsala, Sweden) that had been equilibrated with medium containing (in mM) 145 NaCl, 10 HEPES, 5 KCl, 5 glucose, and 1 MgSO 4 (pH 7.4) at room temperature.…”
Section: Subjectsmentioning
confidence: 99%
“…R min was then determined by the addition of 10 mM EGTA after adjustment of pH to 8.3 with 30 mM Tris. Corrections were applied for extracellular fura 2 leaked from platelets because of EGTA usage and for autofluorescence by subtracting the fluorescence values of the unloaded platelets and test reagents (21,22). Rapid initial drop in the fluorescence signal at 340 nm after EGTA addition was considered to reflect the contribution of the extracellular dye as extracellular Ca 2ϩ was chelated.…”
Section: Subjectsmentioning
confidence: 99%
“…No significant differences were found in body weight after each treatment, suggesting that amlodipine nor cilazapril did affect growth of SHR. Furthermore, methodological issues are important to assess the Ca 2 handling in fura-2-loaded platelets (6)(7)(8)(9). In this study, no significant differences were found in intracellular fura-2 concentration, Rmax and Rmin suggesting that we can safely compare the calculated [Ca 2 ]i in fura-2-loaded platelets among all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cytosolic calcium concentration ([Ca 2 ]i) and abnormal Ca 2 handling have been widely demonstrated in a variety of cell types from patients with essential hyperten-and thrombin-induced aggregation response are increased in platelets from spontaneously hypertensive rats (SHR) (6)(7)(8)(9)(10)(11)(12). However, there is a possibility that the exposure of circulating blood cells to the mechanical shear forces in the circulatory system could alter cellular Ca 2 metabolism or cell function.…”
Section: Introductionmentioning
confidence: 99%